On Horns and Halos: Confirmation Bias and Job Rotation - Daniel Müller (University of Bonn, Bonn Graduate School of Economics (BGSE), 2010)
Confirmation bias, which refers to unintentional and unknowing selectivity in the use of evidence, belongs to the major problems faced by organizations. In this article, we discuss job rotation as a natural solution to this problem. In a nutshell, adopting job rotation provides an organization that is plagued by confirmation bias with a more reliable informational footing upon which to base its decisions. Job rotation, however, also comes with a cost, e.g. a loss of productivity or a disruption of work flows. We study this trade-off and identify conditions under which job rotation and specialization are each optimal.
Keywords: M12; M54; 330; Confirmation Bias; Job Rotation; Work Organization; Entscheidung; Informationsverhalten; Bias; Job Enlargement; Arbeitsorganisation; Theorie